KINERJA TENAGA ADMINISTRASI DALAM PENGELOLAAN ARSIP DI SEKOLAH MENENGAH KEJURUAN SWASTA AL-HARIRI KABUPATEN TEBO - Repindo; Rusmini; Widdah, Minnah El (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Archive management is an essential element in supporting the smooth administration of schools. However, archive management at Al-Hariri Private Vocational High School in Tebo Regency has not been carried out optimally due to limitations in administrative staff and supporting facilities. This study aims to analyze the performance of administrative staff in archive management, identify obstacles, and examine efforts to overcome these obstacles to improve the effectiveness of archive governance. This research employs a qualitative approach with a case study design, utilizing observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results indicate that the performance of administrative staff is not yet optimal, as evidenced by unsystematic archive arrangement and the absence of a dedicated archive room. The main obstacles include limitations in human resources and infrastructure. Efforts to overcome these obstacles have been implemented through internal collaboration, more organized manual archive arrangement, effective time management, support from the school principal, competency improvement through training, and the initial implementation of document digitization. This study emphasizes the need to enhance administrative staff competencies, provide adequate archival facilities, and strengthen school administrative management to ensure more effective archive management.